Systematic risk of islamic reits and conventional reits in Malaysia - Mohamed Razali, Muhammad Najib (American Real Estate Society, 2015)
In this paper, we evaluate the systematic risks of Islamic real estate invest- ment trusts (REITs) and conventional REITs in Ma- laysia for the period from August 3, 2005 to De- cember 19, 2014. Our results show that IREITs have lower systematic risks than other conven- tional REITs. The results are consistent when sto- chastic betas are estimated using time-varying co- efficient models. We also find that new IREIT entry creates significant risk reduction effects for the con- ventional REIT markets. When we test the effects of the conversion of Axis REIT from a conventional REIT to an IREIT, we find that the systematic risks of Axis REIT significant reduce between the peri- ods ''before'' and ''after'' the conversion. The find- ings imply that the lower betas of IREITs could pro- tect IREIT investors against stock market volatilities that could not be diversified away.